PENINGKATAN KETERAMPILAN INSTALASI PERANGKAT KERAS KOMPUTER SEBAGAI SARANA PENINGKATAN KOMPETENSI SISWA SMK MAGANG - Wiryajati, I Ketut; Adnyani, Ida Ayu Sri; Putra, I Ketut Perdana; Seniari, Ni Made; Yadnya, Made Sutha; Satiawan, I Nyoman Wahyu (Universitas Mataram, 2025)
Occupational Safety and Health (OSH) is a fundamental aspect to ensure the security and continuity of academic activities, especially in technical laboratory environments that are highly prone to fire hazards. The Electrical Engineering Laboratory of the Faculty of Engineering, University of Mataram, is identified as a high-risk area due to the use of high-voltage electricity, electronic devices, and flammable materials. According to the fire triangle theory comprising fuel, heat, and oxygen fires can be prevented by eliminating one of these elements. A primary preventive effort in this context involves the use of fire extinguishers (APAR) and adequate training on their proper use. This study aims to evaluate the effectiveness of APAR training and awareness campaigns among active laboratory students. The training method applied an andragogical approach with the PASS technique (Pull, Aim, Squeeze, Sweep), accompanied by pre- and post-tests, simulated fire suppression, and participatory observation. Results showed a significant improvement in students’ understanding, with the average score increasing from 18.75% to 88.38% and the standard deviation decreasing from 9.22 to 6.16, indicating more uniform comprehension among participants. A paired t-test revealed a highly significant difference (p < 0.0001), and one-way ANOVA supported that the training had a measurable effect on all evaluated aspects. Beyond cognitive gains, students also demonstrated positive affective and psychomotor responses through active participation and practical suggestions, such as improving extinguisher placement and adding usage instructions. These findings indicate that the APAR training program not only enhances technical knowledge but also cultivates a culture of safety within the academic environment. It is recommended that such training be institutionalized as part of the laboratory's integrated OSH management system